Simultaneous enhanced antibacterial and osteoblast cytocompatibility performance of Ti6Al7Nb implant by nano-silver/graphene oxide decorated mixed oxide nanotube composite - Rafieerad, Ali Reza; Bushroa, Abdul Razak; Nasiri-Tabrizi, Bahman; Baradaran, Saied; Amiri, Ahmad; Saber-Samandari, Saeed; Khanahmadi, Soofia; Zeimaran, Ehsan; Basirun, Wan Jefrey; Kalaiselvam, Kaveena; Vellasamy, Kumutha Malar; Vadivelu, Jamuna (Elsevier, 2019)
The self-ordered architecture allows for the exact design and control of geometrical features, to achieve materials with unique properties. For this reason, mixed oxide nanotube arrays have been highly regarded by the scientific community in recent years. In the present study, a hybrid approach of an optimized physical vapor deposition magnetron sputtering (PVDMS), electrochemical anodization as well as spin coating is proposed to improve the mechanical properties, corrosion resistance, antibacterial and osteoblast cytocompatibility performance of Ti6Al7Nb implant (Ti67IMP). Accordingly, controlled decorations of mixed oxide nanotube with silver nanoparticles/graphene oxide (AgNPs/GO) were designed to assess the biofunctionality of the modified Ti6Al7Nb implant. The results show that the surface modification has dramatically reduced the viability of Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) cells. Besides, the AgNPs/GO loaded mixed oxide nanotube has significantly promoted cell adhesion and spreading, compared to the bare substrate. The proposed hybrid approach can also be extended to fabricate highly complex nanoarchitectures with controlled shape and biofunctionality for various orthopedic applications. © 2019 Elsevier B.V.